Pamela, Volume II - Richardson, Samuel, 1689-1761 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pamela, Volume II" by Samuel Richardson is a novel published in 1742 as the sequel to his groundbreaking first work. After marrying the reformed Mr. B, young Pamela must navigate the treacherous waters of upper-class society, reconciling her humble origins with her new exalted position. Through letters and journal entries, she confronts the challenges of social acceptance, class prejudice, and the complexities of married life among the gentry. This continuation explores whether virtue can truly be sustained after its initial reward, examining marriage and social mobility in eighteenth-century England. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Pamela;_or,_Virtue_Rewarded
Release date is 2004-07-20
Produced by Steve Harris and PG Distributed Proofreaders
Keywords: Didactic fiction; England -- Fiction; Epistolary fiction; Master and servant -- Fiction; Kidnapping victims -- Fiction; Virtue -- Fiction; Women household employees -- Fiction